(untitled) (Academia Journal of Medicine, 2019)
Background: The incidence of Dengue has grown dramatically around the world in recent decades. Year after year, the prevalence of the disease is on a rise. This study is designed to study the clinical and laboratory parameters of Dengue patients in a tertiary care teaching hospital. Subjects and Methods: Prospective observational study was undertaken in a tertiary care teaching hospital. This study was carried out for a period of two years between Jan 2017 to December 2018.Seventy-two patients were studied and analyzed. All patients with positive NS1 antigen and positive ELISA test were included in the study. Clinical, hematological and biochemical parameters were noted.Results: Of the 72 patients, majority were females (52.8 %). Fever was the most common symptom followed by other symptoms like head ache, myalgias etc. Conclusion: Dengue is an important cause of mortality and morbidity in our country. Early diagnosis and prompt management can have a positive effect on the outcome of the disease. Proper monitoring of the clinical and biochemical parameters and necessary intervention can bring down the mortality rates associated with this disease.